The Impact of Halal Tourism on Local Economic and Cultural Development in Southern Thailand - Heembo, Mutsaree; Nuyeam, Hadee (Business and Investment Review, 2025)
This study examines the impact of halal tourism on the local economy and cultural development in the southern provinces of Thailand, specifically Pattani, Yala, and Narathiwat. Halal tourism, catering to the needs of Muslim travelers, has emerged as a growing sector that offers significant economic potential and opportunities for cultural preservation. Using a mixed-methods approach, the research analyzes both quantitative data on tourism revenue, employment, and infrastructure development, as well as qualitative insights from local businesses, government officials, and community members. The findings reveal that halal tourism contributes to local economic growth by boosting tourism revenue, creating jobs, and encouraging infrastructure investment. Socially and culturally, it helps preserve local Muslim traditions while fostering community engagement. However, challenges related to cultural authenticity and the equitable distribution of tourism benefits remain. The study concludes with policy recommendations to streamline halal certification processes, enhance infrastructure, and engage local communities in tourism planning, aiming to ensure sustainable and inclusive growth. The research offers valuable insights for policymakers, businesses, and stakeholders looking to develop halal tourism as a driver of economic and cultural prosperity in southern Thailand.